Farmers, Traders and Households' Preference to IVegRI’s Open-Pollinated Chili Varieties in Lembang, West Java, Indonesia - Asma Sembiring; Laksminiwati Prabaningrum; Tonny Koestoni Moekasan (Caraka Tani: Journal of Sustainable Agriculture, 2022)
The majority of Indonesian farmers plant open pollinated (OP) chili because the seed price is affordable. However, the chili has weaknesses, such as the productivity is lower and the seed is not uniform. Indonesian Vegetables Research Institute (IVegRI) attempts to create high-quality OP chili varieties that farmers could access. The study aimed to identify farmers, traders and households’ preferences for OP chili varieties that IVegRI has released. The study was carried out in Lembang Sub-district, West Java Province, Indonesia, from March to November 2019. A total of 82 respondents, consisting of farmers, traders and households, were asked about their preference for three OP chili varieties, namely Tanjung, Carvi and Ciko. The respondents were selected purposively. Data were analyzed using perceived quality. The results of this study have revealed that production per plant was the most important chili attribute for farmers, while fruit shape and color were the most essential chili attributes for traders and households, as evidenced by the final scores of 4.93, 4.83 and 4.45, respectively. Traders preferred Tanjung chili variety, as indicated by a score of 1.04. Meanwhile, the farmers and households preferred Carvi to Tanjung and Ciko varieties, with a score of 1.05. Farmers' preference for Carvi for all attributes was higher than the average among varieties, especially for production per plant and fruit weight. This implies that Carvi, as the IVegRI OP chili variety, can be disseminated widely to other locations in West Java and other provinces in Indonesia. The findings of this study are expected to provide useful information for a better understanding of factors necessarily considered to further improve IVegRI's OP chili varieties.